2015
DOI: 10.1245/s10434-014-4239-8
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Preoperative Lymph Node Enlargement in Intrahepatic Cholangiocarcinoma: A Multi-Institutional Study by the Kyushu Study Group of Liver Surgery

Abstract: Preoperative evaluation of LNM proved to be difficult, and survival time in ICC patients with lymph node enlargement was prolonged as a result of hepatectomy. Thus, ICC patients with preoperative lymph node enlargement should not be prematurely deemed non-curative cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 22 publications
2
46
1
Order By: Relevance
“…Data from our group and others have emphasized the importance of assessing the lymph node basin to stage patients accurately. 9,[25][26][27] The finding that lymph node metastasis were strongly associated with risk of extrahepatic recurrence serves to emphasize the importance of assessing the regional nodal basins. While lymph node metastasis may indeed portend a higher risk of extrahepatic recurrence and indicate the need for adjuvant therapy, postoperative therapy unfortunately remains largely ineffective.…”
Section: Discussionmentioning
confidence: 99%
“…Data from our group and others have emphasized the importance of assessing the lymph node basin to stage patients accurately. 9,[25][26][27] The finding that lymph node metastasis were strongly associated with risk of extrahepatic recurrence serves to emphasize the importance of assessing the regional nodal basins. While lymph node metastasis may indeed portend a higher risk of extrahepatic recurrence and indicate the need for adjuvant therapy, postoperative therapy unfortunately remains largely ineffective.…”
Section: Discussionmentioning
confidence: 99%
“…One study showed a positive predictive value for metastatic disease of 67% in round lymph nodes exceeding 18 mm which are rare [17]. Another study used positron emission tomography-computed tomography (PET-CT) and concluded that preoperative evaluation remains difficult [18] while a recent metaanalysis demonstrated PET-CT imaging to be accurate in the evaluation of primary tumors, lymph node and distant metastasis [19]. The most recent article found lymph node enlargement with a small axis diameter exceeding 1 cm in preoperative imaging as the strongest predictor for histopathological lymph node metastases [20].…”
Section: Introductionmentioning
confidence: 99%
“…The ability to preoperatively predict lymph node status would be very useful in deciding therapeutic strategies for ICC patients. However, the majority of reports have concluded that predicting lymph node metastasis from preoperative imaging is difficult for biliary cancers …”
Section: Introductionmentioning
confidence: 99%
“…However, the majority of reports have concluded that predicting lymph node metastasis from preoperative imaging is difficult for biliary cancers. [16][17][18][19] Carbohydrate antigen (CA)19-9 was originally isolated from a culture medium of a human colorectal cancer cell line by Koprowski et al 20,21 in 1979 and is widely known as a useful biomarker in the diagnosis of several adenocarcinomas, including cholangiocarcinoma. [22][23][24][25] In addition, some reports have identified preoperative serum CA19-9 (s-CA19-9) level as an independent prognostic factor in ICC patients.…”
Section: Introductionmentioning
confidence: 99%